Practical approach to the diagnosis of adult-onset leukodystrophies: an updated guide in the genomic era. Issue 5 (22nd November 2018) - Lynch, David S; Wade, Charles; Paiva, Anderson Rodrigues Brandão de; John, Nevin; Kinsella, Justin A; Merwick, Áine; Ahmed, Rebekah M; Warren, Jason D; Mummery, Catherine J; Schott, Jonathan M; Fox, Nick C; Houlden, Henry; et al.
Abstract : Adult-onset leukodystrophies and genetic leukoencephalopathies comprise a diverse group of neurodegenerative disorders of white matter with a wide age of onset and phenotypic spectrum. Patients with white matter abnormalities detected on MRI often present a diagnostic challenge to both general and specialist neurologists. Patients typically present with a progressive syndrome including various combinations of cognitive impairment, movement disorders, ataxia and upper motor neuron signs. There are a number of important and treatable acquired causes for this imaging and clinical presentation. There are also a very large number of genetic causes which due to their relative rarity and sometimes variable and overlapping presentations can be difficult to diagnose. In this review, we provide a structured approach to the diagnosis of inherited disorders of white matter in adults. We describe clinical and radiological clues to aid diagnosis, and we present an overview of both common and rare genetic white matter disorders. We provide advice on testing for acquired causes, on excluding small vessel disease mimics, and detailed advice on metabolic and genetic testing available to the practising neurologist. Common genetic leukoencephalopathies discussed in detail include CSF1R, AARS2, cerebral arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL), and mitochondrial and metabolic disorders.